Coordinated roles of SLX4 and MutSβ in DNA repair and the maintenance of genome stability. (4th March 2021) - Young, Sarah J.; West, Stephen C.
Abstract: SLX4 provides a molecular scaffold for the assembly of multiple protein complexes required for the maintenance of genome stability. It is involved in the repair of DNA crosslinks, the resolution of recombination intermediates, the response to replication stress and the maintenance of telomere length. To carry out these diverse functions, SLX4 interacts with three structure-selective endonucleases, MUS81-EME1, SLX1 and XPF-ERCC1, as well as the telomere binding proteins TRF2, RTEL1 and SLX4IP. Recently, SLX4 was shown to interact with MutSβ, a heterodimeric protein involved in DNA mismatch repair, trinucleotide repeat instability, crosslink repair and recombination. Importantly, MutSβ promotes the pathogenic expansion of CAG/CTG trinucleotide repeats, which is causative of myotonic dystrophy and Huntington's disease. The colocalization and specific interaction of MutSβ with SLX4, together with their apparently overlapping functions, are suggestive of a common role in reactions that promote DNA maintenance and genome stability. This review will focus on the role of SLX4 in DNA repair, the interplay between MutSβ and SLX4, and detail how they cooperate to promote recombinational repair and DNA crosslink repair. Furthermore, we speculate that MutSβ and SLX4 may provide an alternative cellular mechanism that modulates trinucleotide instability.